Commenters as political actors infringing on the field of journalism. (11th June 2019) - Wolfgang, J. David
Abstract : Journalists see online commenters as outsiders who are a potential threat to the reputation and legitimacy of professional journalism. But should commenters be seen as potential new journalistic agents, or are they serving a political role? This study uses field theory to consider how online commenters at one large news organization engage in promoting ideology and how journalists respond. Commenters see themselves as the duty-bound defenders of political perspectives rarely seen in media. Journalists see this as a threat to their profession. The potential political role for the online commenter in journalism is discussed.